Certain subclasses of Bazilevič functions of type α - Shigeyoshi Owa; Milutin Obradovic (International Journal of Mathematics and Mathematical Sciences)
Certain subclasses B(α,β) and B1(α,β) of Bazilevič functions of type α are introduced. The object of the present paper is to derive a lot of interesting properties of the classes B(α,β) and B1(α,β).